Pengaruh Psikoedukasi terhadap Kecemasan Keluarga Pasiend di IGD RSUD Jampang Kulon - Desi Mustikarani; Ernawati Hamidah; Hadi Abidillah; Asep Suryadin (Universitas Malahayati Lampung, 2025)
ABSTRACT Anxiety experienced by patients' families in the Emergency Room (ER) can negatively affect medical decision-making and interactions with healthcare providers. Psychoeducation is one approach that can help families manage anxiety by increasing their knowledge and understanding of the patient's condition and the emergency service process. This study aims to determine the effect of psychoeducation on the anxiety levels of patients' families in the ER of Jampang Kulon Regional General Hospital. The study used a quasi-experimental design with a pretest-posttest control group approach. A total of 32 respondents were randomly divided into intervention and control groups, with 16 participants in each group. The intervention group received psychoeducation, while the control group received no treatment. The research instrument used was the Hamilton Anxiety Rating Scale (HARS). Wilcoxon test results showed a significant decrease in anxiety levels after psychoeducation was given (p-value = 0.001), and the Mann-Whitney test indicated a significant difference between the intervention and control groups after the intervention (p-value = 0.000). The study concludes that psychoeducation is effective in reducing anxiety levels among patients' families in the ER. This intervention is expected to become a nursing strategy to improve the comfort and emotional stability of patients' families in emergency settings. Keywords: Psychoeducation, Anxiety, Patients' Families, Emergency Room. ABSTRAK Kecemasan yang dialami keluarga pasien di Instalasi Gawat Darurat (IGD) dapat berdampak negatif terhadap pengambilan keputusan medis dan interaksi dengan tenaga kesehatan. Psikoedukasi menjadi salah satu pendekatan yang dapat membantu keluarga mengelola kecemasan melalui peningkatan pengetahuan dan pemahaman tentang kondisi pasien serta proses pelayanan di IGD. Penelitian ini bertujuan untuk mengetahui pengaruh psikoedukasi terhadap tingkat kecemasan keluarga pasien di IGD RSUD Jampang Kulon. Desain penelitian yang digunakan adalah quasi eksperimen dengan pendekatan pretest-posttest control group design. Sampel berjumlah 32 responden, dibagi secara acak menjadi kelompok intervensi dan kelompok kontrol, masing-masing 16 orang. Intervensi berupa pemberian psikoedukasi diberikan kepada kelompok intervensi, sedangkan kelompok kontrol tidak menerima perlakuan. Instrumen penelitian menggunakan kuesioner Hamilton Anxiety Rating Scale (HARS). Hasil uji Wilcoxon menunjukkan adanya penurunan tingkat kecemasan yang signifikan setelah diberikan psikoedukasi (p-value = 0,001), dan uji Mann-Whitney menunjukkan perbedaan signifikan antara kelompok intervensi dan kontrol setelah intervensi (p-value = 0,000). Kesimpulan dari penelitian ini adalah psikoedukasi efektif dalam menurunkan tingkat kecemasan keluarga pasien di IGD. Diharapkan intervensi ini dapat dijadikan strategi keperawatan dalam meningkatkan kenyamanan dan stabilitas emosional keluarga pasien di ruang gawat darurat. Kata Kunci: Psikoedukasi, Kecemasan, Keluarga Pasien, Instalasi Gawat Darurat